Crack Cocaine-Induced Cardiac Conduction Abnormalities Are Reversed by Sodium Bicarbonate Infusion - Carlos Henrique Miranda; Antônio Pazin-Filho (Case Reports in Medicine)
We report a dramatic case of a 19-year-old man with crack cocaine overdose with important clinical complications as cardiac arrest due to ventricular fibrillation and epileptics status. During this intoxication, electrocardiographic abnormalities similar to those found in tricyclic antidepressant poisoning were observed, and they were reversed by intravenous sodium bicarbonate infusion.